Prostate cancer and supportive care: a systematic review and qualitative synthesis of men's experiences and unmet needs. (29th January 2015) - King, A.J.L.; Evans, M.; Moore, T.H.M.; Paterson, C.; Sharp, D.; Persad, R.; Huntley, A.L.
<x xml:space="preserve">Abstract</x> Prostate cancer is the second most common cancer in men worldwide, accounting for an estimated 1.1 million new cases diagnosed in 2012 (www.globocan.iarc.fr). Currently, there is a lack of specific guidance on supportive care for men with prostate cancer. This article describes a qualitative systematic review and synthesis examining men's experience of and need for supportive care. Seven databases were searched; 20 journal articles were identified and critically appraised. A thematic synthesis was conducted in which descriptive themes were drawn out of the data. These were peer support, support from partner, online support, cancer specialist nurse support, self‐care, communication with health professionals, unmet needs (emotional support, information needs, support for treatment‐induced side effects of incontinence and erectile dysfunction) and men's suggestions for improved delivery of supportive care. This was followed by the development of overarching analytic themes which were: uncertainty, reframing, and the timing of receiving treatment, information and support. Our results show that the most valued form of support men experienced following diagnosis was one‐to‐one peer support and support from partners. This review highlights the need for improved access to cancer specialist nurses throughout the care pathway, individually tailored supportive care and psychosexual support for treatment side effects.